Evsey Domar and Russia - Mauro Boianovsky (Duke University, Center for the History of Political Economy (CHOPE), 2021)
The paper discusses Evsey Domar's role as a link between economics in the West and in Russia. The Russian heritage he brought with him from Harbin (Manchuria) to the US consisted of an interest in socialism and Russian history. He paid close attention to the 1947 Varga controversy in the USSR. Domar's rediscovery of Feldman's (1928) growth model in 1957 brought it to the attention of Western and Soviet economists alike. Soviet economic development was also discussed in his interpretation of Preobrazhensky's (1926) work on agricultural and industrial sectors. His 1966 seminal article on producer cooperatives called attention to TuganBaranovsky's 1915 book on the topic. Domar's interest in history resulted in his 1970 hypothesis about the origins of serfdom and slavery. Soviet economists paid some attention to Domar's growth models, especially those involving depreciation and the time structure of capital goods.
Keywords: B22; B24; N00; 330; Domar; Russia; economic growth; socialism; economic history